Why do scientists cheat? Insights from behavioral economics - Necker, Sarah (Review of Social Economy, 2016)
Based on a review of the books by Wible (2014), Stephan (2012), and Lanteri and Vromen (2014), I discuss three different ways in which behavioral economics can enrich the understanding of scientific misbehavior. First, behavioral economics suggests that economic theories of scientific misbehavior, such as the one by Wible (2014), should consider moral costs of cheating, i.e. costs that arise from an individual’s desire to do the “right thing.” Second, behavioral economics demonstrates several ways in which the features of the reward scheme in science,as described by Stephan (2012), can favor cheating. Her conclusion that shirking is rarely an issue in science seems optimistic. Third, behavioral economics indicates that individual characteristics matter for cheating. According to Lanteri and Vromen (2014), economists possess different characteristics than other researchers. Hence, the reaction to incentives may differ across disciplines. Considering these insights is important to assess how a goal such as the pursuit of truth can be achieved efficiently.
CRIS-Team Scopus Importer:2022-05-03
Keywords: behavioral economics; Economics of science; scientific misbehavior